MARKET CAPITALIZATION AND FACTORS OF ITS DETERMINATION – THE CASE OF REPUBLIC OF MACEDONIA - DIANA BOSHKOVSKA; ELIZABETA DJAMBASKA; VLADIMIR PETKOVSKI; VESNA GEORGIEVA SVRTINOV (Annals of the University of Petrosani: Economics)
The development of the capital market considered thru the market capitalization coefficient (in total amount and in percentage changes) in relation with the GDP of the Republic of Macedonia is the subject of research of this paper. The analysis identifies and explains the factor of capital market development. The focus of the paper is to determine the effects of different factors on the capital market development in the Republic of Macedonia. For these purpose a multivariate linear regression is conducted using the data from 1997-2013. The analysis indicates that the capital market in the Republic of Macedonia is small and underdeveloped. Therefore the economic growth factors taken into consideration for the research have not shown considerable impact on the capital market due to its underdevelopment.